Antimyelin antibodies and the risk of relapse in patients with a primary demyelinating event. Issue 6 (16th May 2006) - Rauer, S; Euler, B; Reindl, M; Berger, T
Abstract : Aim: To investigate whether the presence of serum antibodies against myelin oligodendrocyte glycoprotein (MOG) and myelin basic protein (MBP) in patients with a clinically isolated syndrome (CIS) predicts the interval to develop more frequently and earlier a first relapse (clinically definite multiple sclerosis: CDMS) than seronegative patients. Methods: Sera from 45 patients with a CIS and positive intrathecal IgG-synthesis were retrospectively tested for the presence of IgM antibodies against both MOG and MBP. Antibodies were detected by immunoblot using recombinant MOG (1–125) and human MBP antigen preparations. Clinical follow ups were performed retrospectively by telephone interviews and documented neurological examination. Results: Using the Cox proportional hazards model there was no significant increased risk for developing CDMS in anti-MOG and anti-MBP positive patients compared with negative. However regarding the median of the time span between CIS and CDMS over the whole follow up, antibody positive patients (MOG/MBP +/+) developed significantly earlier relapses (median 5.5 months (range 3–20)) than the antibody negative ones (median 25.0 months (range 7–43); p<0.006). On testing sera from 56 apparently healthy students, quite high frequencies of anti-MOG and anti-MBP antibodies (21% and 28% respectively) were detected. This limited specificity of anti-MOG and anti-MBP antibodies has been seen earlier and restricts their diagnostic relevance in MS despite their role as a predictor of relapses after a CIS. Conclusions: This study confirms previous data only in a subanalysis indicating that patients with positive anti-MOG/MBP antibodies develop earlier relapses than patients who are antibody negative. However, the authors could not verify that the presence of these antibodies anticipates the overall risk of developing CDMS—according to study criteria—after a first demyelinating event within the study period of 21–106 months (mean 60 (SD 25)).